2005
DOI: 10.1038/sj.onc.1209283
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of microRNA expression patterns in hepatocellular carcinoma and non-tumorous tissues

Abstract: MicroRNAs (miRNAs) are a non-coding family of genes involved in post-transcriptional gene regulation. These transcripts are associated with cell proliferation, cell differentiation, cell death and carcinogenesis. We analysed the miRNA expression profiles in 25 pairs of hepatocellular carcinoma (HCC) and adjacent nontumorous tissue (NT) and nine additional chronic hepatitis (CH) specimens using a human miRNA microarray. Targets and references samples were co-hybridized to a microarray containing whole human mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
784
2
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,058 publications
(829 citation statements)
references
References 22 publications
(20 reference statements)
33
784
2
10
Order By: Relevance
“…2,12 They found five downregulated types of miRNA, including miR-145, and emphasized that the finding of decreased miR-145 expression was consistent with the finding that miR-145 was one of the most frequently downregulated types of miRNA in 16 prostatectomy specimens in the study by Ozen et al 10 Decreased miR-145 expression has been described in lung caner, breast cancer and hepatocellular carcinoma. 17,18 In addition, the expression of miR-145 has consistently been found to be decreased in the adenomatous and cancer stages of colorectal cancer. 19,20 Porkka et al 11 reported that miR-145 was downregulated in PCa compared with BPH.…”
Section: Discussionmentioning
confidence: 99%
“…2,12 They found five downregulated types of miRNA, including miR-145, and emphasized that the finding of decreased miR-145 expression was consistent with the finding that miR-145 was one of the most frequently downregulated types of miRNA in 16 prostatectomy specimens in the study by Ozen et al 10 Decreased miR-145 expression has been described in lung caner, breast cancer and hepatocellular carcinoma. 17,18 In addition, the expression of miR-145 has consistently been found to be decreased in the adenomatous and cancer stages of colorectal cancer. 19,20 Porkka et al 11 reported that miR-145 was downregulated in PCa compared with BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, dysregulation of miR-16, miR-195 and miR-497 have also been found in a range of other cancers, including chronic lymphocytic leukaemia, prostate, pancreas, cervical carcinomas together with sarcomas and benign uterine leiomyomata (Table 4). 12,[53][54][55][56][57][58][59][60][61][62][63] Little is known about the mechanisms of micro-RNA deregulation in neoplastic tissue. MicroRNA genes are commonly located at minimal regions of amplification, loss of heterozygosity and breakpoint regions, suggesting that abnormal microRNA profiles can be caused by somatic gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…By using array-based technology and reverse transcription (RT)-PCR, the global miRNA expression profiles as well as the level of individual miRNA species have been analyzed in various human cancers, and aberrant miRNA expression was found in all tumor types studied to date, including hematological malignancies, 6 lymphoma, 7 melanoma, 8 glioblastoma, 9,10 as well as epithelial cancers from lung, 11,12 breast, 13,14 colon, 15,16 liver, 17,18 thyroid, [19][20][21][22] pancreas [23][24][25][26] etc. When compared to their normal-tissue counterparts, both overexpression and underexpression of miRNA has been observed, with decreased expression appearing to be more common in some studies, 8,27 leading to the hypothesis that oncogenes might be target genes for these miRNAs.…”
mentioning
confidence: 99%